A new human leukocyte antigen class I allele: HLA‐A*02:374. Issue 1 (6th December 2012) - De Zorzi, M.; Caggiari, L.; Crovatto, M.; Talamini, R.; Garziera, M.; De Re, V.
<x xml:space="preserve">Abstract</x> HLA‐A*02:374 differs from HLA‐A*02:01:01 by one amino acid change at codon 112 where G is replaced by V.